A study on the Chinese nuclear energy options and the role of ADS reactor in the Chinese nuclear expansion. (August 2016) - Fiori, F.; Zhou, Z.
Abstract: China has the advantage of learning from the mistakes made by nations that have developed their nuclear power energy system in the last century. Such mistakes encompass the lack of sustainable development of the nuclear energy and poor planning in the back-end of the nuclear fuel cycle. The present paper studies the evolution of a double strata cycle with fast reactor gradually replacing the LWR. It starts from 2035 and covers the historical development of nuclear energy in China to the year 2100. The paper studies the ADS impact on the NFC and estimates the number and the deploying schedule of the ADS reactors to limit the accumulation of minor actinides. The other aspects considered here are natural uranium resources, fuel utilization efficiency, proliferation and diversion risks, spent fuel production and overall materials flow. Additionally, perturbation calculations were performed to evaluate the impact of the uncertainty on key parameters. The results are discussed in view of the Chinese nuclear fuel cycle plan and their policy implications are thoroughly evaluated. Highlights: A reference future nuclear fuel cycle scenarios is simulated. The ADS and FRs impact on the future Chinese nuclear fuel cycle is studied. Sensitivity calculations have been performed to asses various uncertainties. The whole NFC materials flow is assessed. Energy Policy implication of the results are discussed.